Correction of heat-induced susceptibility changes in respiratory-triggered 2D-PRF-based thermometry for monitoring of magnetic resonance-guided hepatic microwave ablation in a human-like in vivo porcine model. (31st December 2022) - Hensen, Bennet; Hellms, Susanne; Werlein, Christopher; Jonigk, Danny; Gronski, Phillip Alexander; Bruesch, Inga; Rumpel, Regina; Wittauer, Eva-Maria; Vondran, Florian W. R.; Parker, Dennis L.; Wacker, Frank; Gutberlet, Marcel
Abstract: Purpose: To develop and evaluate susceptibility corrected 2D proton resonance frequency (PRF)-based magnetic resonance (MR)-thermometry for the accurate assessment of the ablation zone of hepatic microwave ablation (MWA). Methods and materials: Twelve hepatic MWA were performed in five LEWE minipigs with human-like fissure-free liver. Temperature maps during ablation of PRF-based MR-thermometry were corrected by modeling heat induced susceptibility changes. Ablation zones were determined using cumulative equivalent minutes at 43 °C (CEM43) as tissue damage model. T1 weighted (w) post-ablation contrast-enhanced (CE) MR-imaging and manually segmented postmortem histology were used for validation. The agreement of uncorrected (raw) and susceptibility corrected (corr) MR-thermometry with T1w post-ablation CE MR-imaging and histology was evaluated. The Wilcoxon-signed rank test and Bland–Altman analysis were applied. Results: With the susceptibility corrected MR-thermometry a significantly increased dice coefficient (raw: 77% vs. corr: 83%, p  < 0.01) and sensitivity (raw: 72% vs. corr: 82%, p  < 0.01) was found for the comparison to T1w-CE imaging as well as histopathology (dice coefficients: raw: 76% vs. corr: 79%, p  < 0.001; sensitivity: raw: 72% vs. corr: 74%, p  < 0.001). While major axis length was significantly increased (7.1 mm, p  < 0.001) and minor axis length significantly decreased (2.2 mm, p  < 0.001) in uncorrected MR-thermometry compared to T1w-CE MR-imaging, no significant bias was found after susceptibility correction. Conclusion: Using susceptibility corrected 2D PRF-based MR-thermometry to predict the ablation zones of hepatic MWA provided a good agreement in comparison to T1w post-ablation CE MR-imaging and histopathology.